1999
DOI: 10.1007/s002170050443
|View full text |Cite
|
Sign up to set email alerts
|

The influence of starter culture selection on sauerkraut fermentation

Abstract: The rate of pH decrease during cabbage fermentation and the biogenic amine content of sauerkraut could be positively influenced by the application of starter cultures. Fermentation temperature and salt concentration also have a significant effect on the process. In the selection of starter strain the biogenic amine production should be considered for histamine and also total amine production. Lactobacillus curvatus 2775 did not show any histamine synthesis and resulted in low total amine values on MRS medium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 8 publications
2
31
1
Order By: Relevance
“…Some strains of LAB, which are frequently involved in cabbage fermentation, such as Lactobacillus spp., Lactobacillus curvatus, Leuconostoc mesenteroides and Pediococcus damnosus, have proved to have important amino acid decarboxylase activity (Halász, Bárath, & Holzapfel, 1999;Moreno-Arribas, Polo, Jorganes, & Muñoz, 2003;ten Brink et al, 1990;Voigt & Eintenmiller, 1977). Furthermore, Halász et al (1994) and Halász et al (1999), observed that the applied starter cultures may affect the production of biogenic amines during fermentation. Hence, the biogenic amine formation observed in sauerkrauts obtained in the present work may be mainly attributed to the metabolic activity of L. plantarum and L. mesenteroides used as starter cultures.…”
Section: Discussionmentioning
confidence: 96%
“…Some strains of LAB, which are frequently involved in cabbage fermentation, such as Lactobacillus spp., Lactobacillus curvatus, Leuconostoc mesenteroides and Pediococcus damnosus, have proved to have important amino acid decarboxylase activity (Halász, Bárath, & Holzapfel, 1999;Moreno-Arribas, Polo, Jorganes, & Muñoz, 2003;ten Brink et al, 1990;Voigt & Eintenmiller, 1977). Furthermore, Halász et al (1994) and Halász et al (1999), observed that the applied starter cultures may affect the production of biogenic amines during fermentation. Hence, the biogenic amine formation observed in sauerkrauts obtained in the present work may be mainly attributed to the metabolic activity of L. plantarum and L. mesenteroides used as starter cultures.…”
Section: Discussionmentioning
confidence: 96%
“…KIRSCHBAUM et al (1997KIRSCHBAUM et al ( , 1999 found extremely high amounts of putrescine in bottled and pasteurised sauerkraut juices from Germany (up to 229 or 694 mg/dm For the preparation of sauerkraut with lowered biogenic amines content the initial fermentation should run at a temperature of 15-20°C and bacterial activity can be suppressed by pasteurisation as soon as total acidity reaches the value 9-10 g (as lactic acid) per kg or at the pH value 4.0-3.8 (KALAČ et al 1999). Some researchers found out that an increase in histamine concentration went parallelly with pH values below 3.8-3.6 and therefore suggested to stop the fermentation process by pasteurisation when pH decreased below 4 (HALÁSZ et al 1999) because in this stage the activity of the yeasts Pediococcus cerevisiae started that can produce histamine at a concentration of about 200 mg/kg (KOLESÁROVÁ 1995). KALAČ et al (2000b) reported that sauerkrauts inoculated by Lactobacillus plantarum or a mixed culture of Lactobacillus plantarum, Lacto-bacillus casei, Enterococcus faecium and Pediococcus spp.…”
Section: Occurrence Of Biogenic Amines In Lactic Acid Fermented Vegetmentioning
confidence: 99%
“…Using these methods, histamine can be determined by o-phthaladehyde and tyramine by β-naphthol (Ascar & Treptow, 1986). At suitable conditions amino acid analyzer can be used not only for the determination of BAs as well their representative precursor amino acids (Halasz et al, 1999). Recently due to the commercial availability of enzymes like MAO and putrescine oxidase, several research groups tried to couple the enzymatic reactions with electrochemical sensors in order to obtain simple and reproducible biosensors.…”
Section: Analytical Methods For the Detection Of Biogenic Amines In Foodmentioning
confidence: 99%